2012
DOI: 10.1111/j.1445-2197.2012.06149.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of diagnosis and surgical approach for Mirizzi syndrome

Abstract: Ultrasound, MRCP and endoscopic retrograde cholangiopancreatography in combination with choledochoscope procedure in operation could improve the diagnostic sensitivity of Mirizzi syndrome. Intraoperative choledochoscope is effective to confirm Mirizzi syndrome during operation. Open surgery is the current standard for managing patients with Mirizzi syndrome. Laparoscopic surgery should be confined to Mirizzi syndrome type I and patients should be selected very strictly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 17 publications
1
74
1
1
Order By: Relevance
“…Therefore, it is important to have the MS in the differential diagnosis of obstructive jaundice. 11 In the literature, the idea that the majority of patients present pain in the epigastric or right upper quadrant (60% to 100%), jaundice (50% to 100%), and elevated liver enzymes 10 is reinforced. In our series the most common finding was mucocutaneous jaundice (82.8%), most frequent than abdominal pain (Table 1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is important to have the MS in the differential diagnosis of obstructive jaundice. 11 In the literature, the idea that the majority of patients present pain in the epigastric or right upper quadrant (60% to 100%), jaundice (50% to 100%), and elevated liver enzymes 10 is reinforced. In our series the most common finding was mucocutaneous jaundice (82.8%), most frequent than abdominal pain (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…12 The mean presentation age of MS is high compared with the rest of analyzed series. [9][10][11][12][13] It is noteworthy that in recent years we are experiencing an increase of numbers of cholecystectomy in older patients with gallstones, because of increased life expectancy. This situation, combined with the characteristics of patients who come to our reference unit, may justify our series.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge in management of MS is in attaining an accurate pre-operative diagnosis. Multiple studies have studied the rates of pre-operative diagnosis of MS based on the classification proposed by Csendes et al [2] with highly variable rates of accurate pre-operative imaging diagnosis ranging from 8 to 82% [3, 9-11]. …”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of ERCP, on the other hand, was lower at 65.9%. However, it remains a valuable adjunct because it allows delineation of the level and extent of biliary obstruction, as well as closer evaluation of ductal abnormalities, including fistulae [9]. Furthermore, ERCP allows the application of sphincterotomies or biliary stent insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The management was according to the stage of Mirizzi's syndrome: leaving a part of gallbladder infundibulum adherent to the bile duct after excision of its mucosa, or closing the fistula opening by using two flaps of the wall of gallbladder on both sides of the fistula after destruction or excision of mucosa, with inserting a Ttube through the bile duct. In previous studies, open operations for Mirizzi's syndrome was accepted as standard because the reported incidence rate of conversion to open cholecystectomy was remarkably high, with a range of 37% to 78% (19). In our study, all cases were completed by laparoscopic cholecystectomy without any injury to the bile ducts.…”
Section: Discussionmentioning
confidence: 81%